PUBLIC EDUCATION AND PENSIONS IN DEMOCRACY: A POLITICAL ECONOMY THEORY. Issue 5 (11th July 2016) - Lancia, Francesco; Russo, Alessia
Abstract: A dynamic political economy theory of fiscal policy is presented to explain the simultaneous existence of public education and pensions in modern democracies. The driving force of the model is the intergenerational conflict over the allocation of the public budget. Successive generations of voters choose fiscal policies through repeated elections. The political power of elderly voters creates the motive for adults to support public investment in the human capital of future generations since it expands future pension possibilities. We characterize the Markov perfect equilibrium of the voting game in a small open economy. The equilibrium reproduces salient features of intergenerational fiscal policies in modern economies.